Transmission of tuberculosis from smear negative patients: a molecular epidemiology study. Issue 4 (26th March 2004) - Hernández-Garduño, E; Cook, V; Kunimoto, D; Elwood, R K; Black, W A; FitzGerald, J M
Abstract : Background: While smear positive patients with tuberculosis (TB) are considered more infectious than smear negative patients, the latter can also transmit TB. Methods: In a molecular epidemiology study of 791 patients in the Greater Vancouver regional district, the number of episodes of TB transmission from two groups of smear negative clustered patients by RFLP (assumed to be involved in recent transmission) was estimated after assessing for potential bias. Group 1 (n = 79) included patients with pulmonary TB or pulmonary + extrapulmonary disease (PTB or PTB+EPTB); group 2 (n = 129) included all patients in group 1 + extrapulmonary cases alone. Results: In the total sample the mean (SD) age was 51 (21) years, 54.3% were male, and 17.0% of patients were clustered. Compared with smear negative patients, smear positive patients were more likely to be in a cluster (OR = 2.0, 95% CI 1.1 to 3.6) and to have had a history of ethanol abuse (OR = 2.7, 95% CI 1.0 to 6.7), diabetes mellitus (OR = 2.8, 95% CI 1.1 to 7.0), injection drug use (OR = 3.1, 95% CI 1.1 to 8.3), and to have had a previous hospital admission (OR = 8.5, 95% CI 5.1 to 14.0). The proportion of episodes of transmission from smear negative clustered patients ranged from 17.3% to 22.2% in group 1 and from 25% to 41% in group 2. Conclusion: In Greater Vancouver, smear negative cases appear responsible for at least one sixth of culture positive episodes of TB transmission.